ACHIEVING SUSTAINABLE DEVELOPMENT THROUGH COMMUNITY-BASED RENEWABLE ENERGY PROJECTS IN NIGERIA (Intent Research Scientific Journal, 2024)
The study aimed to examine the current state of community-based renewable energy projects in Nigeria and assess their impact on sustainable development goals. A mixed-methods approach was employed, including surveys, interviews, and case studies of existing community-based renewable energy initiatives. The research findings indicate that while community-based renewable energy projects are still in their early stages in Nigeria, they hold significant potential for sustainable development. The findings of this research contribute to the understanding of community-based renewable energy projects for sustainable development in Nigeria. They provide valuable insights for policymakers, energy practitioners, community leaders, and other stakeholders in developing strategies and frameworks to scale up community-based renewable energy initiatives. By promoting community ownership, local participation, and sustainable energy practices, these projects can play a crucial role in Nigeria's transition to a more sustainable and resilient energy future, ultimately driving inclusive and sustainable development across the country.